EFEKTIVITAS PEMBERIAN IZIN TRAYEK ANGKUTAN UMUM (STUDY DI DINAS PERHUBUNGAN KOTA MANADO) - Lapian, Friedrick Napoleon; Rumapea, Patar; Ogotan, Martha (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT: Department of transportation is implementing elements of Manado city Manado CityGovernment, led by the head of Department, and responsible to the Mayor through the Regional Secretary(Minister of the Interior decision/autonomous region no. 55 in 2000). Follow-up the decision haspublished regulations Manado number 04 of 2008 about the Organization and the work area of the city ofManado, Manado city and regulation number 19 in 2008 about the details of the duties and functions ofthe Office of the city of Manado in the relationship of carrying out the functions of the service to thecommunity. Department of transportation supporting role as Manado city in creating organizationrelationships ensure the safety, security, public order and the smooth comfort as well as environmentalsustainability.This study uses qualitative methods, data sources or informants research as many as 10 peoplewere taken from several elements, namely the Department of transportation employee Manado 3 persons,owner of microlet 4 people and 3 people microlet user community. Data collection using observation,interviews, and documentation.Conclusion based on the results of this research, it can be recommended in general suggestionsfor the Department of transportation the city of Manado, the effectiveness of the Service relationship ofManado city is still pretty good, to enhance the effectiveness of the Department of transportation should begood increases the production of standards and the feasibility of a public transport vehicle to vehicle inmicrolet extend stretch permit has a decent road standards and make convenience for users of publictransport. Quality of work should be improved again in this case about extension of the public transportroute permit is expected to Transport service to be more selective and further improve the qualitystandards of the PC in public transit ride. Efficiency also needs to be improved, i.e. public transport testingmicrolet if just past standard test feasibility of KIR can be seen many vehicles that are not worthy of theroad still passes the test of KIR, better than the Department of transportation's own re-testing against themicrolet public transport will extend the public transport route permit in order to generate a convenientpublic transit vehicles. the satisfaction of the society is in the specified test standards of microlet publictransport last so if you want people to feel satisfied with the performance of the Department oftransportation in this permit extension routes should improve testing the feasibility of an above standardof yesteryear. The service has been good but needs to be improved any more time in processing theextension of route license, because the owner of the vehicle also feels no need to wait long to getpermission for these routes and also affects the intentions of owners of public transport vehicles toannually renew stretch licenses.Key Words: Effectiveness, Department Of Transportation, Route Clearance.